Rancang Bangun Aplikasi Rekrutmen Dan Seleksi Karyawan Berbasis Website Pada Pt Sasmita Abadi Gloves - Sahla Salsalbila Arza Saat; Henry Bambang Setyawan; A. B. Tjandrarini (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
PT Sasmita Abadi Gloves is the first manufacturing company in Indonesia that exports the glove industry. At PT Sasmita Abadi Gloves there are 2 parts, namely the production section and the non-production section. Gloves PT Sasmita Abadi requires new employee candidates every year, therefore, to get competent and quality employees, the company needs to carry out a process of embracing prospective employees. During the recruitment process carried out by PT Sasmita Abadi Gloves, it experienced several obstacles, one of which was that the incoming application was still in the form of physical or paper data and the applicant had to come directly to the company to deliver or submit the application file. The solution that can be given is to make an employee recruitment and selection application, because this application can help HRD solve existing obstacles. Based on the results of the application trial, it produces a report recording the results of an employee search. This application generates calculations using the graphic rating scale method, where the photographic selection assessment uses a scale of 1 to 5. System testing uses the black box testing method which produces information that the application is appropriate and has run according to its function, while for testing using the user acceptance test in general the results testing is acceptable to users.